Analisis Keefektifan Pendekatan Matematika Realistik untuk Meningkatkan Motivasi Belajar Matematika Siswa - Lilis Arini; Dewi Purnama Sari (Fakultas Keguruan dan Ilmu Pendidikan, Universitas Kristen Indonesia, 2023)
The purpose of this research is to find out whether students' motivation to learn mathematics can be increased by using a realistic mathematics approach. With a total of 26 students, this research was conducted during an odd semester of the 2022/2023 academic year. This research uses a qualitative descriptive research type. In trial I, the average score of the questionnaire on students' motivation to learn mathematics was 73.51 percent. In trial II, the average score of the questionnaire on students' motivation to learn mathematics increased to 84.61%. Students' motivation to learn mathematics with a realistic approach increased by 9.83 percent based on the results of trial I and trial II. Thus, it can be concluded that the realistic mathematical approach is effective in increasing students' motivation towards learning mathematics.